REVIEWS OF THE POLISH PRESS ABOUT THE UKRAINIAN THEATER THE NAME OF IVAN TOBILEVICH IN STANISLAV (1921-1931) - Tsivkach, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is devoted to the analysis of the Ukrainian theater in Stanislav and based on little-known reviews published in Polish newspapers in 1921-1931.